Parapharyngeal Schawannnoma. Case Report: Schwanoma Parafaringeo. Reporte de caso - Moyano Navarro, Enrique (2021)
Parapharyngeal tumor lesions present a low incidence, representing between 0,5 and 0,8% of all head and neck tumors. Approximately 80% show benign behavior. The uniqueness of these lesions derives from their complex anatomical situation and the symptoms with which they usually appear, being in most cases nonspecific and almost always derived from the compressive effect produced by the lesion on the oropharynx and the oropharynx. Schwannomas of the parapharyngeal space are very rare tumors that originate from the sheath of schawnn, generally slow growing, and are usually asymptomatic. Treatment is surgical, often complex due to the anatomical location.The case of a 42-year-old female patient with a diagnosis of Schwannoma in the left parapharyngeal region, demonstrated by incisional biopsy, is presented; undergoing surgical treatment, which was carried out without complications.